Effects of Rifaximin on Bacterial Translocation in Thioacetamide-Induced Liver Injury in Rats - Harputluoglu, Murat M. M.; Demirel, Ulvi; Gul, Mehmet; Temel, Ismail; Gursoy, Sule; Selcuk, Engin Burak; Seckin, Yuksel (Springer/Plenum Publishers, 2012)
Intestinal bacterial overgrowth (IBO) and increased mucosal permeability are suggested to increase bacterial translocation (BT) in liver injury. Rifaximin (RIF) is a minimally absorbed oral antimicrobial agent that restores gut microflora imbalance. The aim of the present study was to investigate the effects of RIF on BT frequency in thioacetamide (TAA)-induced liver injury. Group 1 was the control. In group 2 (TAA), rats received TAA daily for 3 days. In group 3 (TAA + RIF), RIF was commenced on the same day as the first dose of TAA. In group 4 (RIF), rats received only RIF. Ileal aspirate Escherichia coli counts were significantly lower in the TAA + RIF group than in TAA group. There was no difference in BT frequency between the TAA and TAA + RIF groups. Our results suggest that factors such as intestinal barrier dysfunction and impaired host immune shield, apart from IBO, play an important role in BT in this model.
Keywords: rifaximin; bacterial translocation; thioacetamide; liver injury